Pengaruh Biaya Kepatuhan, Pemeriksaan Pajak dan Penerapan E-SPT Terhadap Kepatuhan Wajib Pajak Badan pada KPP Pratama Denpasar Barat - Joannete Maria Cimpatara De Joman; Ida I.D.A.M. Manik Sastri; Luh Kade Datrini (Jurnal Riset Akuntansi Warmadewa, 2020)
Compliance of taxpayers is the behavior of a taxpayer in carrying out tax obligations and using their rights while still adhering to the applicable tax laws and regulations. The purpose of this study is to understand the effect of compliance costs, tax audits and the application of e-SPT to corporate taxpayer compliance at the West Denpasar KPP. Data collection techniques were carried out with a questionnaire and the number of samples used was 94 respondents. The data analysis technique used is multiple linear regression analysis. 1) Compliance costs have a negative and not significant effect on taxpayer compliance, this is evidenced by the tcount obtained by the compliance fee of -1.525 with Sig. = 0.131> 0.05. 2) Examination of tax has a negative and significant effect on compliance of taxpayers as evidenced by the t-value obtained by the compliance fee of -2,567 with Sig. = 0.012